The international scoring system (ISS) for multiple myeloma remains a robust prognostic tool independently of patients' renal function - Dimopoulos, M.A.; Kastritis, E.; Michalis, E.; Tsatalas, C.; Michael, M.; Pouli, A.; Kartasis, Z.; Delimpasi, S.; Gika, D.; Zomas, A.; Roussou, M.; Konstantopoulos, K.; et al. (Annals of Oncology, 2012)
Background: The International Staging System (ISS) is the most widely used staging system for patients with multiple myeloma (MM). However, serum β2-microglobulin increases in renal impairment (RI) and there have been concerns that ISS-3 stage may include 'up-staged' MM patients in whom elevated β2-microglobulin reflects the degree of renal dysfunction rather than tumor load. Patients and methods: In order to assess the impact of RI on the prognostic value of ISS, we analyzed 1516 patients with symptomatic MM and the degree of RI was classified according to the Kidney Disease Outcomes Quality Initiative-Chronic Kidney Disease (CKD) criteria. Results: Forty-eight percent patients had stages 3-5 CKD while 29% of patients had ISS-1, 38% had ISS-2 and 33% ISS-3. The frequency and severity of RI were more common in ISS-3 patients. RI was associated with inferior survival in univariate but not in multivariate analysis. When analyzed separately, ISS-1 and ISS-2 patients with RI had inferior survival in univariate but not in multivariate analysis. In ISS-3 MM patients, RI had no prognostic impact either in univariate or multivariate analysis. Results were similar, when we analyzed only patients with Bence-Jones >200 mg/day. Conclusions: ISS remains unaffected by the degree of RI, even in patients with ISS-3, which includes most patients with renal dysfunction. © The Author 2011. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved.
Keywords: age; Albumin; Creatinine; Lactate dehydrogenase; Survival; β2-microglobulin